Peningkatan Keterampilan Perempuan di IOM Surabaya dalam Pembuatan Produk Sabun Cuci Piring - Aristawidyana Salsabila; Dyana Putri Widiyanti; Virana Mega Putri; Riyan Oktaviano Sanggara; Naufal Amirullah; Ricky Alejandro Martin (Nuban Jaggadhita Center, 2025)
This Community Service aims to improve the ability of mothers in the IOM (International Organization for Migration) environment in Sawotratap, Sidoarjo, in making their own dishwashing soap with simple technology. The methods used include direct training, demonstrations and joint practice using environmentally friendly and cost-effective materials. Based on the results of the implementation, it was seen that the participants experienced an increase in knowledge and skills in the process of making the soap. In addition, this activity also opens up opportunities for participants to save money, if possible, they can develop small businesses from home. It is hoped that this activity can be the first step in supporting the creative economy in the community.